The role and significance of scientific collaboration for the new emerging sciences - Groboljšek, Blanka (Teorija in praksa, 2014)
The article addresses some issues related to the definition and analysis of scientific collaboration. Starting with a general presentation of studies on Slovenian co-authorship networks of researchers in four different disciplines, the article seeks to ascertain if there are any differences between disciplines that are more committed to the "Mode 1" production of knowledge and disciplines more committed to the "Mode 2" production of knowledge. The research is based on a bibliometric analysis of co-authorship networks, a quantitative web survey among scientists and qualitative interviews among a small group of leading representatives of the scientific community and R&D policy institutions in Slovenia.
Keywords: Cooperation; scientific method; Scientific research; Scientists; Slovenia; Slovenija; Sodelovanje; Znanstveniki; Znanstveno raziskovanje